2017
DOI: 10.1016/j.dyepig.2017.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the five multistate species of the anthocyanin analog 7-β-D-glucopyranosyloxy-4′-hydroxyflavylium to the β-cyclodextrin derivative captisol

Abstract: Binding of the five multistate species of the anthocyanin analog 7-b-D-glucopyranosyloxy-4 0-hydroxyflavylium to the b-cyclodextrin derivative captisol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The selectivity of CD toward more hydrophobic species has been widely explored to devise many different stimuli responsive systems using guest molecules that change their polarity or ionization state upon application of stimuli such as light, redox potential, temperature, or added chemicals. , In this context, synthetic flavylium compounds were found to be excellent candidates for photoresponsive host–guest cyclodextrin-based systems owing to their potential to interconvert between neutral and charged species using light inputs. …”
Section: Stimuli-responsive Host–guest Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selectivity of CD toward more hydrophobic species has been widely explored to devise many different stimuli responsive systems using guest molecules that change their polarity or ionization state upon application of stimuli such as light, redox potential, temperature, or added chemicals. , In this context, synthetic flavylium compounds were found to be excellent candidates for photoresponsive host–guest cyclodextrin-based systems owing to their potential to interconvert between neutral and charged species using light inputs. …”
Section: Stimuli-responsive Host–guest Systemsmentioning
confidence: 99%
“…The influence of β-CD complexation on the kinetics and thermodynamics of the network of reactions involving different synthetic flavylium derivatives was investigated in great detail using different techniques, including NMR, ITC, circular dichroism, UV–vis, and stopped-flow. All these studies revealed that, among the flavylium multistate species, the neutral uncolored species (B, Cc, and Ct) bind with higher affinity ( K usually in the 10 3 M –1 range) to the hydrophobic cavity of β-CD while the respective flavylium cations do not bind or show much weaker affinities.…”
Section: Stimuli-responsive Host–guest Systemsmentioning
confidence: 99%
“…The intermediate B may also be confined in SBECD to a smaller extent. A previous study of a structurally similar anthocyanin, 7-β-D-glucopyranosyloxy-4′-hydroxyflavylium complexation with SBECD, demonstrated the largest affinity of the Cc form to the host macrocycle [ 41 ]. We found considerable alteration of the spectrum when the solution containing 20.84 mg/mL SBECD was kept for 3 h in the dark.…”
Section: Resultsmentioning
confidence: 99%
“…[16] The stabilization of naturala nthocyaninsa nd flavylium analogs by developing host-guests ystemsi sp oorly reportedi nt he literature. [17][18][19] In the case of cyclodextrins, ad e-stabilization of the red flavyliumc ation generally occursb ecause the colorless hemiketals pecies is preferentially encapsulated by the receptor.T ot he best of our knowledge,d endrimers have never been used as hosts for color tuning of anthocyanins with pH. Ar ecent study demonstrated the use of silica-PAMAM [poly(amidoamine)] dendrimer nanoparticles to encapsulate anthocyanins and to further evaluated their antiproliferative activity against neuroblastoma( Neuro 2A).…”
Section: Introductionmentioning
confidence: 99%
“…Several hosts have been described for inclusion of guest molecules such as crown ethers, porphyrins, cyclodextrins, cucurbiturils, nanoparticles and nanotubes, liposomes, and dendrimers . The stabilization of natural anthocyanins and flavylium analogs by developing host–guest systems is poorly reported in the literature . In the case of cyclodextrins, a destabilization of the red flavylium cation generally occurs because the colorless hemiketal species is preferentially encapsulated by the receptor.…”
Section: Introductionmentioning
confidence: 99%